Efficient extraction of small microplastic particles from rat feed and feces for quantification. Issue 1 (January 2023) - Toto, Benuarda; Refosco, Alice; Dierkes, Jutta; Kögel, Tanja
Abstract: To date, microplastic is ubiquitously encountered in the environment. Studies analyzing microplastic in terrestrial ecosystems, including animal feces and feed, are few. Microplastic quantification method validation and harmonization are not yet far developed. For the analysis of small microplastic, approximately <0.5 mm, extraction from organic and inorganic materials is fundamental prior to quantitative and qualitative analysis. Method validation, including recovery studies, are necessary throughout the analytical chain. In this study, we developed an optimized, efficient protocol with a duration of 72 h for the digestion of laboratory rat feed and feces. A combination of a mild acidic (H2 O2 15%; HNO3 5%) and an alkaline treatment (10% KOH) dissolving the previous filter, followed by enzymatic digestion (Viscozyme®L) proved to be efficient for the extraction and identification of spiked polyamide (15–20 μm) and polyethylene (40–48 μm) from feed and feces samples from rats, showing high recovery rates. Extracted rat feces samples from an in vivo study in which Wistar rats were fed with feed containing microplastic were analyzed with pyrolysis-gas chromatography-Orbitrap™ mass spectrometry, quantifying recovered microplastic in rat feces in environmentally relevant concentrations. The presented three-step protocol provides a suitable, time and cost-effective method to extract microplastic from rat feed and feces. Graphical abstract: Image 1 Highlights: Microplastic fed to rats quantified in feces. Extraction of small microplastic from rat feed and feces within two days. Method LOD including extraction process. Circadian rhythm friendly protocol for HSE-compatible high throughput. Avoiding analyte loss by dissolving filter.